Eksplorasi Pendidikan Karakter Era Revolusi Industri 4.0 - Muhammad Ardy Zaini; Moch Shohib (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2020)
Abstract: Cyber ​​technology is another term for education in the era of the industrial revolution 4.0, the emergence of artificial intelligence (IoT) by utilizing Artificial Intelligence